Does Expropriation of Large Shareholders Change Corporate Investment Behaviors? Evidence from Chinese Listed Companies. Issue 3 (2nd July 2020) - Zhang, Jinqing; Chen, Hui; An, Yunbi
ABSTRACT: This paper presents a three-period dynamic model establishing the expropriation-investment relation for firms with financing constraints. Focusing on Chinese listed companies, we find that firms with less tight financing constraints overinvest before expropriation if the intended expropriation level is below a threshold, and underinvest if otherwise, while expropriation in these firms does not impact inefficient investment during and after expropriation even after relevant sanctions are imposed. We also find that expropriation in firms with tight financing constraints has no significant impacts on inefficient investment before expropriation, but further tightens firms' financing constraints during and after expropriation, leading to underinvestment.